OPTIMASI RUTE PENGOLAHAN GAS LAPANGAN âXâ MENGUNAKAN GAS ROUTES CALCULATOR - Deviana, Theresia
Natural gas is an alternative to fullfill energy demand, either domestic needs or export. Field "X", north of Madura Island, has various choices of natural gas utilization. Based on high demand and adequate infrastructure in East Java, gas can be utilized as Gas Power Plant (PLTG) or exported as Liquified Natural Gas (LNG). Moreover, natural gas can also be processed into various products such as city gas, Methanol, Ethylene, Gasoline, Liquified Petroleum Gas (LPG) and Condensate. This final project is determine the best product or route from the scenario of natural gas processing based on economic parameters using net-back calculation method. Economic parameters for determining project feasibility include net-back price and NPV. The best scenario was conducted using GasRoutesCalculator®. Sensitivity studies were conducted to determine the most influential factor such as natural gas, CAPEX, OPEX and IRR. After that, the best route is analyzed from the aspects of economy, technique and regulation.